Stakeholder consensus on the purpose of clinical evaluation of electronic health records is required. Issue 2 (June 2017) - Ericson, Lisa; Hammar, Tora; Schönström, Nils; Petersson, Göran
Abstract: Objective: To explore the purpose and performance of clinical evaluation of electronic health records (EHRs) among stakeholders in order to identify any need for regulatory actions or guidelines. Methods: This was a qualitative study of information collected in semi-structured interviews ( n =28) of representatives of the five largest EHR vendors in Sweden, healthcare provider IT managers, users, and representatives of national authorities. Results: We found a difference between the stated purpose of clinical evaluation of EHRs by the authorities and the perception of the purpose by the vendors, IT managers, and the users. The respondents gave divergent answers about the medical purpose of the application: e.g. availability of data, overview and documentation, patient safety, process efficiency, decision support, a working tool, and an aid to communication and follow-up. Several vendors found it difficult to put the term clinical evaluation in its specific context, instead referring to literature reviews, risk analyses, risk-management processes, acceptance tests, test facilities, pilot tests, and proven experience. Conclusions: Stakeholders need to agree on a mutually acceptable, consistent method to guide regulatory decisions. The lack of consensus regarding the purpose and performance of clinical evaluation of EHRs could impact negatively on a safe and efficient documentation in healthcare. Thus, there is a need for more consistent use of terms and concepts in, and a more systematic approach to, clinical evaluation of EHRs. To ensure that the implementation of IT in healthcare meets expectations, delivers the desired outcome, and does not create new problems, it should be evaluated. Highlights: Perceived purpose and performance of clinical evaluation of EHRs were explored. Uniform definitions of terms and concepts within the area are essential. Regulations and guidelines on the accomplishment of clinical evaluation are needed. Simplified guidance on clinical evaluation is proposed.